Carotenoid intake from natural sources and colorectal cancer: a systematic review and meta-analysis of epidemiological studies. Issue 1 (January 2017) - Panic, Nikola; Nedovic, Darko; Pastorino, Roberta; Boccia, Stefania; Leoncini, Emanuele
Abstract : Carotenoid intake from natural sources has been hypothesized to reduce the risk of colorectal cancer (CRC). The aim of this study was to systematically review the epidemiological evidence for the association between carotenoid intake from natural sources and CRC development. We carried out a systematic review and meta-analysis of epidemiological studies to investigate whether the intake of specific carotenoids from natural sources, as well as combined carotenoids, is associated with the risk of CRC overall and by anatomic subsite. A comprehensive literature search of MEDLINE and Scopus databases was performed. Twenty-two articles were identified from the literature search, of which 16 were case–control studies and 6 were cohort studies. In the random-effects meta-analysis of case–control and cohort studies, we found no association between the intake of individual and total carotenoids and the risk of CRC overall and by anatomic subsite. Overall, our findings do not support a significant association between intake of specific carotenoids from dietary sources, as well as combined carotenoids, and the risk of CRC overall and by anatomic subsite. Abstract : Supplemental Digital Content is available in the text.